Gamification as a tool to rise motivation of studying immunology in a medical university - N. Davidovich V.; E. Bashilova N.; M. Shestakova V.; N. Kukalevskaya N.; Н. Давидович В.; Е. Башилова Н.; М. Шестакова В.; Н. Кукалевская H. (Professional education in the modern world, 2021)
Modern realities make us think about future doctor's motivation raising to study labor-intensive progressively developing disciplines including immunology. Understanding the immune mechanisms and their role in normal and pathological conditions requires students to have deep fundamental knowledge, analytical thinking and spatial representation of the processes occurring at the immune response. Creating a motivated competent personality of a doctor who is able to navigate quickly in a dynamically developing and updating information space, solve medical problems based on acquired competencies, and integrate knowledge and skills from fundamental disciplines to clinical practice is currently a paradigm of medical education. Introducing modern educational technologies, such as gamification (using the game in the educational process) into the pedagogical process increases significantly its effectiveness by raising the student involvement. This article reveals the design of the interactive digital quiz «General Immunology» created base on «Kahoot» service for test and educational project development, and reflects the research results of the game effect on learning and engagement. 112 students of the Medical Faculty of Northern State Medical University (Arkhangelsk) took part in the quiz, 67 (59.8 %) valid questionnaires with «feedback» were received. Most students (86.5 %) reported that the game was useful to study immunology and raised interest in the discipline. Respondents had a positive game perception in terms of fixing terminology in immunology (86.6 %), and structuring the material (86.1 %). Thus, introducing gamification technology can increase the student's motivation to study fundamental and clinical immunology, helps to structure the material and fix complex terminology. Современные реалии заставляют нас задуматься о повышении мотивации будущих врачей к изучению трудоемких, прогрессивно-развивающихся дисциплин, к которым относится иммунология. Понимание иммунных механизмов и их роли в норме и при развитии ...